Cancer, immune suppression and Coronavirus Disease-19 (COVID-19): Need to manage drug safety (French Society for Oncology Pharmacy [SFPO] guidelines). (August 2020) - Slimano, Florian; Baudouin, Amandine; Zerbit, Jérémie; Toulemonde-Deldicque, Anne; Thomas-Schoemann, Audrey; Chevrier, Régine; Daouphars, Mikaël; Madelaine, Isabelle; Pourroy, Bertrand; Tournamille, Jean-François; Astier, Alain; Ranchon, Florence; et al.
Highlights: The COVID-19 pandemic causes unprecedented impact on cancer patients. Cancer patients are greater susceptible to COVID-19 infection and intense symptoms. A rethink of the care pathway is required to reduce the risk of contamination. Oncologists must detect and manage drug-related problems with anti-COVID-19 drugs. Caution is needed about interactions between anticancer and viral experimental drugs. Abstract: The Coronavirus disease (COVID-19) pandemic is disrupting our health environment. As expected, studies highlighted the great susceptibility of cancer patients to COVID-19 and more severe complications, leading oncologists to deeply rethink patient cancer care. This review is dedicated to the optimization of care pathways and therapeutics in cancer patients during the pandemic and aims to discuss successive issues. First we focused on the international guidelines proposing adjustments and alternative options to cancer care in order to limit hospital admission and cytopenic treatment in cancer patients, most of whom are immunocompromised. In addition cancer patients are prone to polypharmacy, enhancing the risk of drug-related problems as adverse events and drug-drug interactions. Due to increased risk in case of COVID-19, we reported a comprehensive review of all the drug-related problems between COVID-19 and antineoplastics. Moreover, in the absence of approved drug against COVID-19, infected patients may be included in clinical trials evaluating new drugs with a lack of knowledge, particularly in cancer patients. Focusing on the several experimental drugs currently being evaluated, we set up an original data board helping oncologists and pharmacists to identify promptly drug-related problems between antineoplastics and experimental drugs. Finally additional and concrete recommendations are provided, supporting oncologists and pharmacists in their efforts to manage cancer patients and to optimize their treatments in this new era related to COVID-19.